A host defense peptide mimetic, brilacidin, potentiates caspofungin antifungal activity against human pathogenic fungi - Thaila Fernanda dos Reis; Patrícia Alves de Castro; Rafael Wesley Bastos; Camila Figueiredo Pinzan; Pedro F. N. Souza; Suzanne Ackloo; Mohammad Anwar Hossain; David Harold Drewry; Sondus Alkhazraji; Ashraf S. Ibrahim; Hyunil Jo; Jorge D. Lightfoot; et al. (Nature Communications, 2023)
Abstract Fungal infections cause more than 1.5 million deaths a year. Due to emerging antifungal drug resistance, novel strategies are urgently needed to combat life-threatening fungal diseases. Here, we identify the host defense peptide mimetic, brilacidin (BRI) as a synergizer with caspofungin (CAS) against CAS-sensitive and CAS-resistant isolates of Aspergillus fumigatus, Candida albicans, C. auris, and CAS-intrinsically resistant Cryptococcus neoformans. BRI also potentiates azoles against A. fumigatus and several Mucorales fungi. BRI acts in A. fumigatus by affecting cell wall integrity pathway and cell membrane potential. BRI combined with CAS significantly clears A. fumigatus lung infection in an immunosuppressed murine model of invasive pulmonary aspergillosis. BRI alone also decreases A. fumigatus fungal burden and ablates disease development in a murine model of fungal keratitis. Our results indicate that combinations of BRI and antifungal drugs in clinical use are likely to improve the treatment outcome of aspergillosis and other fungal infections.